ERG deletions in childhood acute lymphoblastic leukemia with DUX4 rearrangements are mostly polyclonal, prognostically relevant and their detection rate strongly depends on screening method sensitivity - Zaliova, Marketa (Haematologica, 2019)
ERG-deletions occur recurrently in acute lymphoblastic leukemia, especially in the DUX4-rearranged subtype. The ERG-deletion was shown to positively impact prognosis of patients with IKZF1-deletion and its presence precludes assignment into IKZF1(plus) group, a novel high-risk category on AIEOP-BFM ALL trials. We analyzed the impact of different methods on ERG-deletion detection rate, evaluated ERG-deletion as a potential marker for DUX4-rearranged leukemia, studied its associations with molecular and clinical characteristics within this leukemia subtype, and analyzed its clonality. Using single-nucleotide-polymorphism array, genomic polymerase chain reaction (PCR) and amplicon-sequencing we found ERG-deletion in 34% (16 of 47), 66% (33 of 50) and 78% (39 of 50) of DUX4-rearranged leukemia, respectively. False negativity of ERG-deletion by single-nucleotide-polymorphism array caused IKZF1(plus) misclassification in 5 patients. No ERG-deletion was found outside the DUX4-rearranged cases. Within DUX4-rearranged leukemia, the ERG-deletion was associated with higher total number of copy-number aberrations, and, importantly, the ERG-deletion positivity by PCR was associated with better outcome [5-year event-free survival (EFS), ERG-deletion-positive 93% vs. ERG-deletion-negative 68%, P=0.022; 5-year overall survival (OS), ERG-deletion-positive 97% vs. ERG-deletion-negative 75%, P=0.029]. Ultra-deep amplicon-sequencing revealed distinct co-existing ERG-deletions in 22 of 24 patients. In conclusion, our data demonstrate inadequate sensitivity of single-nucleotide-polymorphism array for ERG-deletion detection, unacceptable for proper IKZF1(plus) classification. Even using more sensitive methods (PCR/amplicon-sequencing) for its detection, ERG-deletion is absent in 22-34% of DUX4-rearranged leukemia and does not represent an adequately sensitive marker of this leukemia subtype. Importantly, the ERG-deletion potentially stratifies the DUX4-rearranged leukemia into biologically/clinically distinct subsets. Frequent polyclonal pattern of ERG-deletions shows that late origin of this lesion is more common than has been previously described.